2014
DOI: 10.1155/2014/793238
|View full text |Cite
|
Sign up to set email alerts
|

A Radiative Transfer Modeling Methodology in Gas-Liquid Multiphase Flow Simulations

Abstract: A methodology for performing radiative transfer calculations in computational fluid dynamic simulations of gas-liquid multiphase flows is presented. By considering an externally irradiated bubble column photoreactor as our model system, the bubble scattering coefficients were determined through add-on functions by employing as inputs the bubble volume fractions, number densities, and the fractional contribution of each bubble size to the bubble volume from four different multiphase modeling options. The scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Examples of where spectral simulations were carried out using the FVDOM or DOM methods present a more accurate picture of the functionality of PBRs. For example, [92], conducted simulations on RTE As stated in [92], savings in calculation times can be made with astute choices in solution scheduling.…”
Section: Radiative Transfer Equation Discretisation Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of where spectral simulations were carried out using the FVDOM or DOM methods present a more accurate picture of the functionality of PBRs. For example, [92], conducted simulations on RTE As stated in [92], savings in calculation times can be made with astute choices in solution scheduling.…”
Section: Radiative Transfer Equation Discretisation Approachesmentioning
confidence: 99%
“…Many PBR CFD studies have been found to be lacking with appropriate modelling approaches to solving the full form of the RTE as shown in (3.9). There is strong evidence to suggest that one must take into account the effects of in-scattering [67,69,92,93,97,98]. It was found that the threshold beyond which one must start to consider the effects of in-scattering is 100 mgL −1 dry weight of biomass [97].…”
Section: Summary Of Radiation Modellingmentioning
confidence: 99%